Pyrite nanoparticles derived from mine waste as efficient catalyst for the activation of persulfates for degradation of tetracycline. (April 2021) - Rahimi, Farzaneh; van der Hoek, Jan Peter; Royer, Sebastien; Javid, Allahbakhsh; Mashayekh-Salehi, Ali; Jafari Sani, Moslem
Graphical abstract: Highlights: Mine waste pyrite nanoparticles activated PMS more effectively than PDS. Simultaneous generation of OH and S O 4 - was observed in the pyrite/PMS process. High TTC degradation, relative mineralization and significant detoxification was achieved in the pyrite/PMS process. Pyrite/PMS process could considerably decrease the nephrotoxicity and hepatotoxicity effect of TTC. The catalytic activity of pyrite nanoparticles was remains stable after four consecutive cycles. Abstract: Pyrite mine waste was used as a non-toxic and natural catalyst for the activation of peroxydisulfate (PDS) and peroxymonosulfate (PMS) to oxidize tetracycline (TTC), one of the most extensively used antibiotics worldwide, in contaminated water. The results demonstrated that PMS was activated more effectively than PDS by using pyrite. Scavenging experiments indicated that both OH and SO4 − were the main oxidative species in the pyrite/PMS process, while SO4 − was more dominant. A high degradation of 98.3 % and significant mineralization (up to 46 %) of TTC (50 mg/L) were achieved using pyrite activated PMS at a reaction time of 30 and 60 min, respectively. In-vivo toxicity of raw and pyrite/PMS treated TTC solutions was evaluated using biochemical and histopathological assays. The results revealed that the pyrite/PMS process significantly decreased the nephrotoxicity (90 %) and hepatotoxicity (85 %) effect of TTC. Catalyst reusability was evaluated under cycling conditions. No significant decrease in process efficiency was measured between the first and fourth cycle (<3% decrease in TTC removal). In conclusion, mine waste pyrite nanoparticles can be considered as a non-toxic and clean catalyst to activate PMS for an effective detoxification, degradation, and intermediate mineralization of TTC, as a refractory water pollutant.